Pengembangan Aplikasi Peta Interaktif UNJ Untuk Mahasiswa dan Pengunjung - Sahara, Siti; Wulandari, Monica; Khairunnisa, Fitri (Jurnal Ilmiah Global Education, 2024)
The development of information and communication technology has encouraged changes in maps from two-dimensional forms to interactive maps which are more efficient in conveying information. This research discusses the analysis and development of an interactive map of Jakarta State University (UNJ) using the Canva application. With four campus locations spread across Jakarta, Jakarta State University (UNJ) faces difficulties in providing location information for users. Even though they have a web-based information system, none yet displays spatial information on campus buildings. It is hoped that the development of a web-based interactive map will solve existing challenges. Through a Research and Development (R&D) research method approach, with a 4D model. Creating interactive maps using Canva involves design, template selection, adding text, and integration with website links and Google Maps. The research results show the relevance of making UNJ interactive maps in providing more complete and easily accessible information. This development is expected to increase access to information about campuses and the quality of providing geographic information in the digital era.